Per una integrazione del Codice diplomatico padovano. Documenti dal Fondo Veneto I dell’Archivio Segreto Vaticano (1166-1183) - Stella, Attilio (Scrineum, 2013)
This paper consists in a critical edition of 23 documents (1166-1183), stored in Fondo Veneto I within the Secret Vatican Archive, amongst the papers of the church of S. Giorgio in Braida of Verona, published here as an integration of Andrea Gloria’s Codice diplomatico padovano (1877-1881). Counting on more than 1900 documents and covering a chronology from 6th century to 1183, the Codice is nowadays the most complete collection concerning Padua and its territory in the Middle Ages. Fondo Veneto is a documentary resource including pre-1668 documentation of more than 40 ecclesiastical bodies located in the Serenissima Republic territory. Originally stored in Venice, this corpus was transferred to Vatican City in 1836. This paper’s introduction, besides offering a brief historical contextualization of these 23 documents, passes through different themes, such as the edition of the Codice, the historical and archivistic circumstances of Fondo Veneto and S. Giorgio in Braida, the notarial praxis and the role of notaries in rural areas.